Divergent Thinking and Convergent Thinking in the Mathematical Creative Thinking Process in terms of Student Brain Dominance - Bayu Sukmaangara; Sri Tirto Madawistama (Southeast Asian Mathematics Education Journal, 2021)
Convergent and divergent thinking play an essential role in a person’s creative thinking process to solve problems, which highlights the significance of this research. Aside from that, these two types of thinking are related to the function of the brain’s hemispheres that will affect a person’s perspective in processing information. This research aims to get a view of convergent and divergent thinking in the mathematical creative thinking process in terms of brain dominance. The research was conducted using qualitative method with an exploratory descriptive approach. The instruments used are mathematical creative thinking test, brain dominance tests, and unstructured interviews. The research revealed that left-brain dominant students in the creative thinking process are more prominent in convergent thinking; the balance dominant students in the creative thinking process are balanced in divergent and convergent thinking, while right-brain dominant students in the creative thinking process are more adept in divergent thinking.